Hubungan Antara Beban Kerja Dengan Kelelahan Kerja Pada Pekerja Bagian Produksi Pt. Royal Coconut Desa Kawangkoan Minahasa Utara - Yolanda Tempo, Meysia; Seprianto Maddusa, Sri; B.S. Joseph, Woodford (Pusat Riset dan Inovasi Nasional, 2025)
Background: Work fatigue refers to a condition when workers experience physical or mental fatigue that causes a decrease in their ability to carry out tasks. This fatigue can be influenced by a high workload, and if it continues, it can have an impact on decreasing concentration, productivity, and increasing the risk of work accidents. Objective: This study aims to analyze the relationship between workload and work fatigue in production workers at PT. Royal Coconut, Kawangkoan Village, North Minahasa. Method: This type of research is quantitative research with an analytical observational research design with a cross-sectional approach which was carried out in March-May 2025 involving 94 respondents who had met the inclusion and exclusion criteria. Using a sampling method, namely the total population. The instruments in this study used the Industrial Fatigue Research Committee (IFRC) questionnaire and pulse measurement using a pulse-oximeter. Results: Statistical tests using the Spearman rank test. The results showed that there was a relationship between workload and work fatigue in production workers at PT. Royal Coconut Kawangkoan Village, North Minahasa with a p-value = 0.007 (p < 0.05) Conclusion: it was found that the heavier the workload, the higher the tendency for workers to experience work fatigue.